Roles of peptidyl prolyl isomerase Pin1 in viral propagation - Kanna, Machi; Nakatsu, Yusuke; Yamamotoya, Takeshi; Encinas, Jeffrey; Ito, Hisanaka; Okabe, Takayoshi; Asano, Tomoichiro; Sakaguchi, Takemasa (Frontiers in Cell and Developmental Biology, 2022)
Peptidyl-prolyl isomerase (PPIase) is a unique enzyme that promotes cis-trans isomerization of a proline residue of a target protein. Peptidyl-prolyl cis-trans isomerase NIMA (never in mitosis A)-interacting 1 (Pin1) is a PPIase that binds to the pSer/pThr-Pro motif of target proteins and isomerizes their prolines. Pin1 has been reported to be involved in cancer development, obesity, aging, and Alzheimer's disease and has been shown to promote the growth of several viruses including SARS-CoV-2. Pin1 enhances the efficiency of viral infection by promoting uncoating and integration of the human immunodeficiency virus. It has also been shown that Pin1 interacts with hepatitis B virus proteins and participates in viral replication. Furthermore, Pin1 promotes not only viral proliferation but also the progression of virus-induced tumorigenesis. In this review, we focus on the effects of Pin1 on the proliferation of various viruses and discuss the underlying molecular mechanisms.